Governmentality, the Local State, and the Commons: An Analysis of Civic Management Facilities in Barcelona - Pera, Marina (2022)
This article deploys the Foucauldian concept of governmentality to study the political tensions that may unfold when commons are enacted through hybrid institutional configurations. We focus on civic management facilities (CMFs) that are located in the city of Barcelona. These are facilities owned by Barcelona City Council which, responding to organised citizens’ demands, are transferred to them so that they can develop their own transformative projects for the community. The hybrid institutional nature of these CMFs makes it impossible for them to avoid maintaining a relationship with the local state. Based on a survey to 51 CMFs, semi‐structured interviews with 41 grassroots members of CMFs and seven semi‐structured interviews with public employees and politicians, we argue that hybrid forms of commons lead to the development of political tensions. On the one hand, we show how the local state’s administrative procedures—to do with accountability and the use of public space—reshape the activities of the CMFs, leading to the depoliticisation of their transformative projects. On the other hand, the analysis also presents the strategies of resistance articulated by the facilities, which enable members to work towards the development of their transformative aims. We conclude that such political tensions cannot be resolved but must be properly governed in order to make the commons’ transformative project an enduring one.